Pediatric Life Support: 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations. (November 2020) - Maconochie, Ian K.; Aickin, Richard; Hazinski, Mary Fran; Atkins, Dianne L.; Bingham, Robert; Couto, Thomaz Bittencourt; Guerguerian, Anne-Marie; Nadkarni, Vinay M.; Ng, Kee-Chong; Nuthall, Gabrielle A.; Ong, Gene Y.K.; Reis, Amelia G.; et al.
Abstract: This 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations (CoSTR) for pediatric life support is based on the most extensive evidence evaluation ever performed by the Pediatric Life Support Task Force. Three types of evidence evaluation were used in this review: systematic reviews, scoping reviews, and evidence updates. Per agreement with the evidence evaluation recommendations of the International Liaison Committee on Resuscitation, only systematic reviews could result in a new or revised treatment recommendation. Systematic reviews performed for this 2020 CoSTR for pediatric life support included the topics of sequencing of airway-breaths-compressions versus compressions-airway-breaths in the delivery of pediatric basic life support, the initial timing and dose intervals for epinephrine administration during resuscitation, and the targets for oxygen and carbon dioxide levels in pediatric patients after return of spontaneous circulation. The most controversial topics included the initial timing and dose intervals of epinephrine administration (new treatment recommendations were made) and the administration of fluid for infants and children with septic shock (this latter topic was evaluated by evidence update). All evidence reviews identified the paucity of pediatric data and the need for more research involving resuscitation of infants and children.